Philosophical Foundations of Positive Psychology - Alarcón, Reynaldo (2017)
This paper aims to establish the philosophical framework in which Positive Psychology bases its theoretical assumptions and its view as a philosophy of science. From an ontological standpoint, human beings are the entities investigated through their subjective experience, which is expressed through their behaviors. From the epistemological standpoint, this novel model of psychology is an empirical science, which adopts the hypothetical-deductive model, to determine if its claims have scientific content. From the philosophical anthropology standpoint, Positive Psychology has been influenced by Humanistic Psychology, which considers that humans are unique and unrepeatable beings, who flourish and strive to optimize their inherent psychological potential.